Pemikiran Mistisisme Annemarie Schimmel - Thohir, Umar Faruq (ULUL ALBAB Jurnal Studi Islam, 2012)
Sufism is the unique esoteric way to close to Allah as The Creator of this universe. Sufism teaches its scholars to purify their souls from the sins or something prohibited by Allah, and fulfill them with a good actions and characters. Sufism also coaches its scholars to base their actions with love to Allah, since love to Allah will guide scholars to love all Allah's creations such as like human, animal, tree, and all inside this universe. Loving Allah also drags people to be easy in obeying Allah's commandments where without love, people possibly hard to apply them. In all these terms, Sufism understood by its insiders (scholars) as a doctrine to be closer to AllahÂ  that must be obeyed. In opponent with these insiders, the outsiders acknowledge Sufism is mere tenet that not must be obeyed totally, but can be absorbed and adopted partly. Annemarie Schimmel is one of outsiders Sufism. Schimmel adopted al-Rumi's Sufism taught without becoming Moslem who al-Rumi becomes. Schimmel only looks Sufism from the outside. She judges Sufism as a mystical taught which not only found in Islam, but also in other religions which have a mystical method. That's why she felt not need to be a Moslem, even she adopted and applied al-Rumi's taught, because she did not view al-Rumi as a Moslem teacher but a mystical teacher. Even Schimmel was not a Moslem, but, her study to Sufism should be appreciated, because outsider typically objective in their study.